Bidirectional associations between sensorineural hearing loss and depression and anxiety: a meta-analysis - Zhang, Zhi-qiang; Li, Jing-yang; Ge, Si-tong; Ma, Tian-yi; Li, Fu-yao; Lu, Jun-liang; Si, Shu-rui; Cui, Zhe-zhu; Jin, Yu-lian; Jin, Xiang-hua (Frontiers in Public Health, 2024)
Background: Recently, the prevalence of sensorineural hearing loss (SNL) has been increasing, and several studies have suggested that depression, anxiety, and SNL may be associated with each other, however, individual findings still have discrepancies.To the best of our knowledge, no scholars have systematically elucidated the bidirectional associations between SNL, depression, and anxiety disorders from the perspective of meta-analysis. In this study, we aimed to systematically evaluate the bidirectional associations between SHL and depressive and anxiety symptoms, and to provide evidence-based medical evidence for reducing SNL, depression, and anxiety disorders. Systematic search of PubMed, Embase, and Web of Science databases identified articles published as of June 1, 2023, on the relationship between SNL and depression and anxiety. Meta-analysis was performed to calculate the odds ratios (OR) and 95% confidence intervals (CIs) for the outcome metrics, and the results were combined to assess bivariate associations between the disorders with fixed or random effects. Sensitivity and subgroup analyses were conducted to analyze sources of heterogeneity, and Egger's and Begg's tests combined with funnel plots were applied to assess publication bias.showed that the bidirectional association between SNL and depression and anxiety disorders. The incidence (OR = 0.17, 95% CI: 0.09-0.28) and risk (OR = 1.43, 95% CI: 1.32-1.55) of depression and morbidity were higher in SNL patients than the general population. Elevated prevalence (OR = 0.46, 95% CI: 0.28-0.65) and risk (OR = 1.30, 95% CI: 1.11-1.48) of SNL were also observed in depressed patients. The prevalence of anxiety disorders among SNL patients was about 40% (OR = 0.40, 95% CI: 0.24%-0.57), which was associated with higher risk (OR = 1.83, 95% CI:1.42-2.24) of development than the general population. Incidence of SNL in patients with anxiety disorders was approximately 31% (OR = 0.31, 95% CI: 0.29-0.33).Additionally, subgroup analyses showed that the bidirectional associations between SNL, depression, and anxiety disorders was influenced by age, region, and mode of diagnosis of the disorders (SNL, depression, anxiety).There are bidirectional associations between SNL and depression and anxiety disorders, which was influenced by age and region and the method the disorders (SNL, depression, anxiety) were diagnosed.